Molecular dynamics in electrospun amorphous plasticized polylactide fibers. (2nd September 2015) - Monnier, X.; Delpouve, N.; Basson, N.; Guinault, A.; Domenek, S.; Saiter, A.; Mallon, P.E.; Dargent, E.
Abstract: The molecular dynamics in the amorphous phase of electrospun fibers of polylactide (PLA) has been investigated using the cooperative rearranging region concept. An unusual and significant increase of the cooperativity length at the glass transition induced by the electrospinning has been observed. This behavior is attributed to the singularity of the amorphous phase organization. Electrospun PLA fibers rearrange in a pre-ordered metastable state which is characterized by highly oriented but non-crystalline polymer chains, and the presence of highly cohesive mesophase which plays the role of an anchoring point in the amorphous phase. The successful processing of electrospun fibers of plasticized polylactide is also demonstrated. It is shown that the plasticizer remains in the polymer matrix of the nanofiber after electrospinning. When PLA is plasticized, the loosening of the macromolecules prevails over the preferential orientation of the chains; therefore no mesophase is formed during the electrospinning and the cooperativity length remains the same. When the content of plasticizer increases, the inter-chain characteristic distances estimated from wide angle X-ray scattering (WAXS) are redistributed, suggesting a change in the level of interactions between macromolecules. It is assumed that the resulting decrease of the cooperativity length is driven by the progressive reduction of the number of inter-chain weak bonds. It is shown that in a non-confined environment, the number of structural entities involved in the alpha relaxation is strongly dependent on the level of physical interactions in the amorphous phase. Graphical abstract: Highlights: Successful electrospinning of plasticized and neat polylactide was performed. Cooperativity length in electrospun nanofibers was investigated for the first time. In neat PLA a highly oriented non-crystalline structure with mesophase was generated. An increase of cooperativity due to the mesophase is recorded. Plasticizer annihilates the effect of orientation and decreases the cooperativity.